Improvement of post-thaw quality and fertilizing ability of bull spermatozoa using Rho kinase inhibitor in freezing extender - Behnam, Mina; Asadpour, Reza; Topraggaleh, Tohid Rezaei; Hamali, Hossein (Frontiers in Veterinary Science, 2023)
In this study, it was hypothesized that the addition of an appropriate concentration of Y-27632 (a ROCK inhibitor) to the freezing extender prevents cryopreservation-induced apoptosis and improves embryonic development after in vitro fertilization (IVF). Semen samples were collected from five fertile Simmental bulls using an artificial vagina twice a week for four weeks. Selected samples were pooled and diluted with Tris-egg-yolk-glycerol (TEYG) extender containing different concentrations of Y-27632 (0, 10, 20, 30, and 40 µM) and then frozen in liquid nitrogen. After thawing, computer-assisted semen analysis (CASA), plasma membrane integrity, and acrosome intactness were evaluated in terms of morphological abnormalities, intracellular generation of reactive oxygen species (ROS), DNA fragmentation, phosphatidylserine (PS) externalization, and apoptotic-related gene expression. Finally, groups of frozen and thawed spermatozoa were used for bovine oocyte IVF. The results show that the semen extender at a concentration of 20 µM Y-27632 effectively improved total motility (TM), curvilinear velocity (VCL), as well as the plasma membrane and acrosome integrity compared to the control group (p<0.05). Intracellular ROS levels were significantly (p<0.05) lower in samples treated with 30 µM Y-27632 compared to the control specimen. Furthermore, supplementation of the semen extender with 20 μM Y-27632 resulted in more viable spermatozoa compared with the control group (p<0.05). According to qRT-PCR results, the expression levels of BAX and CASPASE-9 genes in samples treated with 30 μM Y-27632 were significantly downregulated, while the expression of BCL2 was increased compared to the control (p<0.05). The results of IVF demonstrated that the treatment of frozen-thawed spermatozoa with 20 µM Y-27632 increased blastocyst rates compared to the control group (p< 0.05). In conclusion, the addition of 20 µM Y-27632 into the freezing extender can improve the functionality and the fertilizing capacity of frozen spermatozoa due to its antioxidative and anti-apoptotic properties.